Research on Energy Management Control Strategy of MHPA-PV/T Heat Pump System - Wan, Li (International Journal of Electric Power and Energy Studies, 2025)
This article focuses on the MHPA-PV/T heat pump system and studies the energy matching relationship between the power generation and heat generation of the combined heat and power system and the user’s electrical and thermal load requirements. Reasonable operation control strategies are proposed to meet the user’s demand for electricity and suitable temperature water. Selecting the energy consumption period from 20:00 to 21:00 for testing, the feasibility of the selected control strategy was verified, while maximizing the energy utilization efficiency of the system.